The Application of the Jigsaw Type Cooperative Learning Model to Improve Social Science Learning Outcomes - Tiono Kurniawan, Andree; Sudirin, Sudirin; Firnanda, Shinta (Bulletin of Pedagogical Research, 2024)
This research discusses the problem regarding the learning process that has not been achieved. Due to the lack of teachers utilizing varied learning models, it affects student learning outcomes from 22 students who completed 8 students (36.3%) and those who did not complete 14 students (63.6%). The purpose of this research is to find out the improvement of learning outcomes from the use of the jigsaw type learning model in social studies subjects for class IV at MI Muhammadiyah Pekalongan. The researchers used Classroom Action Research (PTK) that is alternative for developing and improving educational practices. PTK uses two cycles consisting of four components, namely planning , action , observation and reflection. By collecting observation data, tests and documentation. The results showed that there was an increase in student learning outcomes for class IV social studies subjects at MI Muhammadiyah Pekalongan, seen in the students' learning mastery at the beginning of 31.8%, the first cycle of the second meeting increased 40.9% and the second cycle of completeness increased to 86.3%. Keywords: Challenge and Orientation Education, Islamic Education, Education at Border Location